(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Each country will force different taxes on individuals and thing so as to attempt developmental work. In India the government of India as of late sanctioned a law to be specific GST. This paper looks to clarify the positive and negative impacts of GST on manufacturing industry in India.The Indian textile industry gives employment to an enormous number of talented and incompetent workers in the country. It contributes about 15 of the all-out annual export, and this value is probably going to increment under GST. GST would influence the cotton value chain of the textile industry including all articles of clothing for people like shirts, pants, saree, attire, shoes and any additionally clothing materials which is picked by most little medium enterprises as it right now pulls in zero focal extract obligation (under discretionary route). It is normal that the tax rate under GST would be higher than the present tax rate for the textile industry. Natural fibers (cotton, wool) which are at present absolved from tax, would be taxed under GST. The Indian leather industry represents around 12.93 percent of the world’s leather creation of concealsskins. The country positions second as far as footwear and leather pieces of clothing generation on the planet and records for 9 percent of the world’s footwear creation. Through this paper we request that the government treat the leather industry on a standard with the textile industry and be exposed to a 5 percent tax no matter how you look at it. Due to both the industries are work concentrated, export arranged, and giving biggest employment opportunities.